HARD SKILL VERSUS SOFT SKILL DALAM PENCAPAIAN KINERJA KARYAWAN PROYEK INFRASTRUKTUR MASS RAPID TRANSIT (MRT) JAKARTA - Iffah Budiningsih; Tjiptogoro Dinarjo Soehari; Marlison Marlison (Akademika : Jurnal Teknologi Pendidikan, 2020)
Optimal employee performance is influenced by factors such as hard-skills and soft-skills. The aim of this research is to identify influence of hard-skill and soft-skills contribute achieving the performance of the Jakarta Mass Rapid Transit (MRT) infrastructure project. The research method using a survey and the number of saturated samples is 57 employees of the Jakarta MRT infrastructure project (from 6 companies consortium). Technique of data analysis is using correlation, simple & multi regression with the SPSS program. The results of this study are following; 1) hard-skills partially influence significantly on the performance of the MRT infrastructure project employees, although only contributed 10% in the achievement of employee performance; 2) the mathematical model Y = 2,284 + 0364 X1 can be used to predict the performance achievement of employees infrastructure projects; 3) soft-skills in partial or simultaneal with hard-skill does not give a real influence on the achievement of employee performance of infrastructure project; 4) for more types of work relying on technic-skills related to high accuracy, the performance of its employees is more influenced by hard-skills; 5) The need to include a soft-skill that is in accordance with the hard-skills learned in the process of learning as a hidden curriculum.